Tłumacz i tłumaczenie z perspektywy normy tłumaczeniowej - Ksenia Gałuskina (Ksiegarnia Akademicka Publishing, 2021)
The Translator and the Translation From the Perspective of the Translation Standard (PN-EN 15038 and PN-EN ISO 17100)